Wilderness: a bridging metaphor for pastoral practice. Issue 1 (2nd January 2016) - Pavey, Emma L.
Abstract : "Not all who wander are lost."—J. R. R. Tolkein In this article, I examine the theme of wilderness in a secular, post-Christendom age from a theological perspective, incorporating inter-disciplinary insights from sociological and cultural sources to synthesize a practical, pastoral application for this theme. I use Charles Taylor's book A Secular Age as a prompt to think about the place of wilderness in the context of such a secular age, both in terms of its literal and metaphorical meanings. I look at some of the ways in which this context impacts the pastoral work of the church, and then at the crucial role of the wilderness motif in Christian Scripture and tradition. We not only discover there the inherent struggles of wilderness experiences, but – crucially – also reveal the wilderness to be a place of spiritual encounter and unique learning where we are accompanied in struggle and offered particular wisdom. Once elaborated in this way as a dangerous yet holy place, we see, finally, how the wilderness theme can be reimagined to mediate the gap between faith and what Taylor calls the immanent frame of the secular age, informing the church's pastoral response to our contemporary cultural context.